(untitled) (BIS Humanities and Social Science, 2026)
This study aims to analyze the influence of Third-Party Funds (DPK), Temporary Syirkah Funds (DST), and Non-Performing Financing (NPF) on the profitability of Islamic Commercial Banks in Indonesia with Financing (P) as an intervening variable. The method used is descriptive analysis, the outer model, and the inner model. The data for this study are the annual reports of Islamic Commercial Banks for five years (2020-2024). The results show that Third-Party Funds (DPK) have no significant effect on Profitability (ROA), while Temporary Syirkah Funds and Non-Performing Financing have a negative and significant effect. Third-Party Funds (DPK) and Temporary Syirkah Funds have a significant positive effect on financing, while Non-Performing Financing has no significant effect. Financing has a significant positive effect on Profitability (ROA), while financing is unable to significantly mediate the relationship between the third independent variable and Profitability (ROA). These findings emphasize the importance of appropriate and efficient Sharia-based fund management in increasing bank profitability.